Turkish Parliamentary Experience Review of the Parliamentary Experience of Turkey from Ottoman to Republic Periods - Saltanat Kydyralieva (Journal of Universal History Studies, 2019)
Turkish parliamentary tradition with a history of 140 years, no doubt is a result of challenging periods which roots extending to the history of the Ottoman Empire. Tanzimat reforms as well as Constitutional Monarchy periods (known as I. and II. Meşrutiyet) crowned with the National Liberation Movement initiated the new political regime in Turkey and formed a parliamentary institution that call now the Turkish parliament or the Grand National Assembly of Turkey. The analysis of the historical evolution of the Turkish parliamentary experience along with its parliamentary functions and activities will provide us valuable information on politics and socio-historical development of the Turkish state. Certainly, the unique characteristics of Turkish society and Turkish history, as well as parliamentary transformations at the global level along with political developments affecting the parliamentary tradition makes a Turkish parliamentary experience noteworthy to be analyzed. Social structure, bureaucracy and traditions of every society or political entity define the role of a parliament in the certain political system. The social and political structure gives important information on the organization and behaviour of the parliament as well as parliamentary functions provide first-hand data on features and characteristics of the society reciprocally. This study is a brief historical account of the Turkish parliament as a representative institution. The main goal of this research is to provide an analytic review of the Turkish parliamentary experience and parliamentary evolution without debates on pro and contras of parliamentary or presidential systems. There are two matching features in our research approach in this study. First, we will focus on and outline the historical evolution process of the Turkish parliamentary experience. Second, we will look for descriptive information to enrich our general understanding of the parliamentary workings. The historical analysis method will be applied to conduct this research. The method was described by sociologist and political scientist Theda Skocpol. The historical analysis method aims to develop and improve descriptive and reasonable hypothesizes on institutions as nation-states.